(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
In the last few decades, there has been a surge of interest in the development of fashion business models to assist fashion companies in reducing the cost and to efficiently manage business processes. These business models are developed to manage the internal operations within the company through adopting complex formulae and algorithms to reduce the waste at each procedure. However in today’s fashion business market, global sourcing and global corporation are much more important than before. The relationship between the fashion company and its suppliers, the relationship between the fashion company and its customers, and the management of these relationships. All of them are crucial parts in the business strategy. The competition between fashion companies is no longer in company level but instead is supply chain versus supply chain. Trying to take the massive information into consideration by using traditional digital technology is not a wise decision when developing business strategy. Further thinking, the information flow through the supply chain has the same characteristics “5Vs” as big data: Volume, Velocity, Variety, Value and Veracity. Put another word: the management of information flow in supply chain is the management of big data. There is no doubt that the digital technology under big data environment will fundamentally change the whole supply chain. The first objective of this paper is to identify the key weakness of lean and agile logistic supply chain models in literature. The second objective is to point out the technology challenges to develop the Tomorrow’s models which build an agile response upon a lean platform: How to set up virtual networks from the early designing stage to the last consuming and feedback stage? How to set up the information standardization and synchronisation process in the system? How to specify the consumer requirements in fitting effects and functional performance of garments? The last objective is to discover the digital technology under big data environment which enable the information efficiently to flow through the whole supply chain.